The ICIDH-2 as a framework for the assessment of functioning and disability in rheumatoid arthritis. Issue 3 (1st March 2002) - Fransen, J; Uebelhart, D; Stucki, G; Langenegger, T; Seitz, M; Michel, B A
Abstract : Objective: To investigate by a cross sectional study in patients with rheumatoid arthritis (RA) the relationship between measures of impairment, activity limitation, and participation of the model of functioning and disability (ICIDH-2). Methods: Inclusion data of patients with RA (n=803) from the Swiss Clinical Quality Management Group were used. Impairments were measured by the Short Form-36 (SF-36) bodily pain scale, rheumatoid arthritis disease activity index (RADAI), disease activity score (DAS28), and radiographic scoring ( x ray). Activity limitation was measured with the Health Assessment Questionnaire (HAQ) and the SF-36 physical functioning scale. Participation was measured with the SF-36 role and social functioning scales. Spearman (partial) correlations were used for analysis. Results: Impairment and activity limitation dimensions of the ICIDH-2 model are related; correlations with the HAQ were: SF-36 bodily pain ( r s =−0.61), RADAI ( r s =0.58), DAS28 ( r s =0.49), and x ray ( r s =0.35). Similar correlations were found for SF-36 physical functioning. Activity limitation and participation restriction dimensions are also related: the HAQ correlates well with SF-36 role-physical ( r s =−0.53) and SF-36 social functioning ( r s =−0.43); SF-36 physical functioning correlates similarly. For impairment and participation restriction dimensions only SF-36 bodily pain is substantially correlated ( r s =0.47 and 0.48) with SF-36 role-physical, after correcting for the influence of the activity limitation dimension (HAQ and SF-36 physical functioning). Conclusions: In this cross sectional study of patients with RA, impairments are associated with activity limitations, and activity limitations are associated with participation restrictions. Pain is the only impairment directly associated with participation restrictions. Based on the results of this study, it is strongly recommended that the ICIDH-2 framework is used in clinical trials and observational studies including the assessment of disease consequences in RA.